Effect of biatomic gas impurities on thermal expansion of fullerite C₆₀ - Dolbin, A.V. (Functional Materials, 2009)
Orientational glasses with gas molecules occupying the octahedral interstitial sites in the C₆₀ lattice have been investigated by the dilatometric method in a temperature interval of 2.5-23 K. At temperatures 4-6 K the glasses undergo a first-order phase transition which is evident from the hysteresis of the thermal expansion and the maxima in the temperature dependences of the linear thermal expansion coefficients α(T) and the thermalization times τ₁(T) of the samples. The effect of the noncentral CO-C₆₀ interaction upon the thermal expansion and the phase transition in these glasses was clarified by comparing the behavior of the properties of the CO-C₆₀ and N₂-C₆₀ solutions.